Effectiveness of Probiotics and Standard Therapy Versus Standard Therapy Alone in Patients of Mild to Moderate Rheumatoid Arthritis: Probiotics and Standard Therapy Vs Standard Therapy Alone in Rheumatoid Arthritis - Iqbal, Gulraiz; Nazar, Tazeen; Aziz, Bilal; Fatima, Tooba; Imran, Yasir; Islam, Asif (Pakistan Journal of Health Sciences, 2024)
Analgesics, steroids and disease modifying anti-rheumatic drugs (DMARDs) are the cornerstone of treatment in rheumatoid arthritis (RA). Objective: To determine effectiveness of probiotics, introduced to standard treatment, in improving Disease Activity Score 28 (DAS-28) in patients with mild to moderate rheumatoid arthritis, when given for a period of three months. Methods: This randomized controlled trial registered under ClinicalTrials.gov ID: NCT06594822, was conducted on diagnosed cases of rheumatoid arthritis presenting to Mayo hospital, Lahore from 24th August 2023 till 23rd February 2024. Eighty-eight patients were recruited employing simple random sampling techniques and were categorized into two groups. Group A received standard therapy along with probiotics whereas Group B received standard therapy alone. DAS-28 score was assessed at baseline, at 45 and 90 days. Results: Patients in Group A showed an effective reduction in DAS-28 of 22.7% compared to 6.8% in group B (p=0.035). DAS-28 score in group A and B at baseline was 3.67 ± 0.61 vs 3.63 ± 0.52, p=0.708, after 45 days was 3.15 ± 0.63 vs 3.49 ± 0.56, p=0.010 and after 90 days was 2.93 ± 0.75 vs 3.27 ± 0.52, p=0.015. During treatment at days 45 and 90, group A patients showed a greater decrease from baseline i.e., -0.52 ± 0.63 vs -0.14 ± 0.56, p<0.010 and -0.74 ± 0.75 vs 0.36 ± 0.52, p<0.015 than group B patients. Group A also had a significant improvement in mean DAS-28 score at days 45 and 90 (p<0.05). Conclusion: Daily supplementation of probiotics with standard treatment is effective for the alleviation of symptoms and disease severity in patients having mild to moderate rheumatoid arthritis.